Drug Administration using Body Area Sensor Network (BASN) - Sindhav, Jignesh B (International Journal of Computer Sciences and Engineering, 2025)
Wireless sensor networks can be defined as a network of sensors which can communicate sans wired networks. The goal of these types of networks is to collect data from different sensors and to forward it to the sink nodes. Body area sensor network (BASN) is a sensor network that can be placed on a human body. The purpose of this research study is to continuously monitor subjects in a hospital and to provide the Physicians and Registered Nurses (RN) with efficient Drug Administration methods by making use of body area sensor networks. If sensor nodes can be connected to medication lists, subject history and the live monitoring feeds of subjects, the possibility of administering and prescribing incorrect medication that might pose serious undesired effects on patients can be countered and mortality rates can be reduced. Thus, this study focuses on implementing sensor nodes on subjects to keep a tab on the allergies and history of diseases the patients might have been subject to and to provide the required medical assistance and the necessary drugs to subdue illnesses.